2013
DOI: 10.1088/0004-637x/766/1/34
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perpetuating Spiral Arms in Disk Galaxies

Abstract: The causes of spiral structure in galaxies remain uncertain. Leaving aside the grand bisymmetric spirals with their own well-known complications, here we consider the possibility that multi-armed spiral features originate from density inhomogeneities orbiting within disks. Using high-resolution N-body simulations, we follow the motions of stars under the influence of gravity, and show that mass concentrations with properties similar to those of giant molecular clouds can induce the development of spiral arms t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
226
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(240 citation statements)
references
References 40 publications
13
226
1
Order By: Relevance
“…In recent years, it was found that the nonlinear effect is significant to understand the overall activity of the spiral arms (e.g., Baba et al 2013;D'Onghia et al 2013). We found that the linear theory can predict the correct pitch angle that is consistent with the numerical simulation.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In recent years, it was found that the nonlinear effect is significant to understand the overall activity of the spiral arms (e.g., Baba et al 2013;D'Onghia et al 2013). We found that the linear theory can predict the correct pitch angle that is consistent with the numerical simulation.…”
Section: Resultssupporting
confidence: 78%
“…This indicates that the leading mode is always generated. We do not discuss the origin of the leading mode here, but it may be generated by some nonlinear processes (e.g., Fuchs et al 2005;D'Onghia et al 2013). The overall evolution of spiral arms cannot be obtained by the linear theory.…”
Section: Linear Analysismentioning
confidence: 99%
“…Finally, this research field has been recently boosted by numerical simulations. N-body solvers are achieving higher and higher resolution and although they are still missing a complete self-consistent understanding of the spiral arm dynamics, several numerical techniques (e.g., the tree-code, Barnes & Hut 1986) allow us to simulate the gravitational interactions among millions of particles with masses of the order of a few thousand solar masses or less (D'Onghia, Vogelsberger & Hernquist 2013;Grand, Kawata & Cropper 2012b,a).…”
Section: Observational Studies Of Density Wave Theorymentioning
confidence: 99%
“…In the last description, spiral arms are transient, recurrent features that wind up and disappear with time, continually being replaced by new transient features that form from small perturbations amplified by a mechanism akin to swing amplification (Goldreich & Lynden-Bell 1965;Julian & Toomre 1966;Toomre 1981;D'Onghia et al 2013). These structures are found to be approximately co-rotating with the disc stars at every radius (e.g., Grand et al 2012a,b), and cause continual radial migration at every radius that manifests as large systematic streaming motions along the spiral arm Hunt et al 2015), which is expected to be different from the peculiar motions induced by density wave spirals.…”
mentioning
confidence: 99%